2018
DOI: 10.1073/pnas.1807405115
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous polymerization and adhesion under hypoxia in sickle cell disease

Abstract: SignificancePatients with sickle cell disease (SCD) suffer from painful vasoocclusive crises. Polymerization of sickle hemoglobin (HbS) in RBCs is generally considered a major contributor to such crisis events. Here, we present the simultaneous and synergistic coupling of adhesion and HbS polymerization. We show that the age of RBCs in circulation plays an important role in mediating this synergistic effect on blood rheology and clinical symptoms. In particular, the youngest RBCs exhibit unique adhesion dynami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
57
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 61 publications
(59 citation statements)
references
References 47 publications
2
57
0
Order By: Relevance
“…Exacerbating the hypoxia‐induced polymerization is the inherent low‐affinity of HbS, presumably due to high levels of 2,3‐diphosphoglycerate (2,3‐DPG) present in sickle RBCs . These sickled RBCs have strongly reduced deformability and show increased adherence to vascular endothelium, leading to vaso‐occlusive crises . Hydroxyurea (HU), regular blood transfusion, and L‐glutamine are the main treatment options in SCD, with allogeneic hematopoietic stem cell transplantation being the only curative therapy currently available .…”
Section: Introductionmentioning
confidence: 99%
“…Exacerbating the hypoxia‐induced polymerization is the inherent low‐affinity of HbS, presumably due to high levels of 2,3‐diphosphoglycerate (2,3‐DPG) present in sickle RBCs . These sickled RBCs have strongly reduced deformability and show increased adherence to vascular endothelium, leading to vaso‐occlusive crises . Hydroxyurea (HU), regular blood transfusion, and L‐glutamine are the main treatment options in SCD, with allogeneic hematopoietic stem cell transplantation being the only curative therapy currently available .…”
Section: Introductionmentioning
confidence: 99%
“…Structurally, the net effect of this Asn-Lys substitution is the removal of the α 2 β 2 -stabilizing Lys132-Glu7 salt bridge, highlighting the perturbation of local electrostatic equilibrium by SCD-linked mutations such as K132N and E6V, too. Previous molecular dynamics simulation studies also suggest that Hb-S polymerization is favoured by inter-facial electrostatic interactions (18), and is inhibited when subjected to hypoxic (low pH environment) conditions, where the side chain of Glu6 gets neutralized and the electrostatic repulsion mechanism disappears. This molecular dynamics simulation study provides a direct support that the electrostatic repulsion mechanism, previously described in (16,19,20), is a key biophysical basis for Hb-S polymerization in RBC sickling, too.…”
Section: Why Is the Electrostatic Repulsion Mechanism So Important Here?mentioning
confidence: 94%
“…Recently, Papageorgiou et al [ 116 ] showed the unique adhesion dynamics of sickle reticulocytes (under hypoxia) (see Figure 6 a–f), the HbS fiber projections can extensively grow outward of the cell boundary, creating multiple adhesion sites. They also showed that not only in reticulocytes, but also in young erythrocytes, adhesion and HbS polymerization can work synergistically to increase the number of adhesion binding sites while the cell is adhered on the surface within minutes.…”
Section: Sickle Cell Diseasementioning
confidence: 99%
“…The aforementioned mechanisms may prove to be factors in initiating or promoting SCD vaso-occlusion. Furthermore, Papageorgiou et al [ 116 ] suggested a connection between polymerization, adhesion, and SS-RBC maturation, which resulted in the following descending order of the degree of adhesion susceptibility under hypoxia: sickle reticulocytes in the circulation ⇒ mature SS-RBCs with low density and high deformability ⇒ mature SS-RBCs with high density and low deformability ⇒ irreversibly-sickled cells.…”
Section: Sickle Cell Diseasementioning
confidence: 99%
See 1 more Smart Citation